Natural products: Regulating glucose metabolism and improving insulin resistance - Fatma S.A. Saadeldeen; Yun Niu; Honglin Wang; Li Zhou; Lijun Meng; Sitan Chen; Dongxiao Sun-Waterhouse; Geoffrey Ivan Neil Waterhouse; Zhenhua Liu; Wenyi Kang (Food Science and Human Wellness, 2020)
Compounds with regulating glucose metabolism and improving insulin resistance (IR) activity are abundant in nature and can be obtained from several sources. They have high potential to be used to treat diabetes mellitus. These compounds isolated from natural plants can be classified seven categories: terpenoids, alkaloids, quinones, flavonoids, phenols, phenyl propanoids, steroids, and other types of compounds. They exert biological effects by different ways and mechanisms. This review illustrated the potential natural products as a rich resource in regulation of glucose metabolism and IR, as well as their mechanisms.